2018
DOI: 10.1016/j.jmps.2018.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Platonic crystal with low-frequency locally-resonant spiral structures: wave trapping, transmission amplification, shielding and edge waves

Abstract: We propose a new type of platonic crystal. The proposed microstructured plate includes snail resonators with low-frequency resonant vibrations. The particular dynamic effect of the resonators are highlighted by a comparative analysis of dispersion properties of homogeneous and perforated plates. Analytical and numerical estimates of classes of standing waves are given and the analysis on a macrocell shows the possibility to obtain localization, wave trapping and edge waves. Applications include transmission am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Discrete systems have been studied to predict crack propagation speed and explain crack tip instabilities [37][38][39][40][41][42]. Enhanced transmission, trapping and wave control with different types of resonators were investigated in [43][44][45][46]. In the present paper, we show how gyroscopic spinners can be implemented in a periodic system supporting flexural waves to stabilize a structure and to tune the filtering properties of the system.…”
Section: Introductionmentioning
confidence: 90%
“…Discrete systems have been studied to predict crack propagation speed and explain crack tip instabilities [37][38][39][40][41][42]. Enhanced transmission, trapping and wave control with different types of resonators were investigated in [43][44][45][46]. In the present paper, we show how gyroscopic spinners can be implemented in a periodic system supporting flexural waves to stabilize a structure and to tune the filtering properties of the system.…”
Section: Introductionmentioning
confidence: 90%
“…Similar localized phenomena may play a substantial role in non-uniform crack propagation as evidenced in (Piccolroaz et al, 2020), where lattice dissimilarity has been shown to promote or diminish localized deformations around the faces of the crack. Trapped modes associated with Rayleigh-Bloch waves in systems incorporating periodic gratings or periodic arrays of resonators were analyzed by Porter and Evans (1999), Porter and Evans (2005), Linton and McIver (2002) and Antonakakis et al (2014) for scalar problems, by Colquitt et al (2015) for vector systems and by Haslinger et al (2017) and Morvaridi et al (2018) for plates.…”
Section: Introductionmentioning
confidence: 99%
“…Li and Li [ 30 ] extended Frandsen et al’s model and included inertial amplification to infinite elastic beams. Other notable implementations include platonic crystals with spiral resonators [ 31 , 32 ], which could emerge as good alternatives due to their low-cost production merits.…”
Section: Introductionmentioning
confidence: 99%